Uterine Isthmocele—A Frequently Overlooked Complication of Cesarean Sections - Rupa, R.; Kushvaha, Suchana; Venkatesh, K. (Indian Journal of Radiology and Imaging, 2021)
Uterine isthmocele or uterine niche is a late complication of cesarean deliveries and causes chronic pelvic pain, menorrhagia or postmenstrual spotting, and infertility. As the number of cesarean sections are constantly increasing, it is important to be aware of this entity so as to make an early diagnosis. This would enable the clinicians to manage these patients efficiently. We present three patients of uterine isthmocele who were evaluated and managed at our institution.
Keywords: cesarean section; defect; isthmocele; myometrium